NEUROLEPTIC MALIGNANT SYNDROME: NEED FOR EARLY DIAGNOSIS AND THERAPY - Khan, Humaira M.; Syed, Nadir A.; Sheerani, Mughis; Khealani, Bhojo; Kamal, Ayeesha; Wasay, Mohammad (Journal of Ayub Medical College Abbottabad, 2006)
Background: Neuroleptic Malignant Syndrome (NMS) is a medical entity that has received little attention in the clinical settings in Pakistan. The aim of our study was to review the predisposing factors, outcomes and characteristics of in-patients diagnosed with NMS. Methods: We performed a retrospective chart review of all cases (age > 15 years) at a tertiary care center in Karachi between January 01, 1990 and November 30, 2001, diagnosed using ICD 10 coding. Data was collected using a standardized data entry form and statistical analysis was performed using Epi Info 6, Version 6.02. Results: There were a total of 20 patients diagnosed with NMS (11 male and 9 female) in our study with a mean age of 46.6±15.9 years. Haloperidol was the most frequently responsible neuroleptic. Of the 18 patients on a neuroleptic, most developed NMS after 8 weeks of therapy. There were 5 mortalities all of which were associated with septic shock. Fourteen patients recovered completely from the episode and did not have any neurologic sequelae. Conclusions: NMS is an important preventable clinical entity. Early diagnosis and judicious use of antipsychotics is warranted to prevent mortality and heightened morbidity. Key Words: Neuroleptic malignant syndrome, antipsychotics, predisposing factors